Review Pesticide Immunoassays: Experience and Future Perspective in Pakistan - Maqbool, Uzma; Qureshi, M. Jamil (Biological Sciences - PJSIR, 2008)
An overview on the use of immunochemical technology for pesticide residue analysis has been described. Pioneering work on the development of pesticide immunoassays (IA) using ELISA technique in Pakistan has been carried out and described in detail. Dieldrin, atrazine and DDT IAs were performed using Enzyme-Linked Immunosorbent Assay (ELISA) kits to determine residual levels of these pesticides in soil and water. ELISA was found to be successful for dieldrin, atrazine and DDT residue analysis. A highly sensitive in-house ELISA has now been developed for atrazine residues determination. Polyclonal antibodies were raised in rabbits by immunization with an atrazine-BSA conjugate and optimized with atrazine-peroxidase (POD) conjugate. It showed middle of the test (50% B/Bo) at 90 ng/l and lowest detection limit (LDL) at 1ng/l in water. For environmental samples, 50% B/Bo was at 75 ng/l and LDL at 4 ng/l. No cross- reactivities were shown by terbutryn, ametryn, des-isopropylatrazine, de-ethylatrazine except terbuthylazine (17%) and hydroxyatrazine (30%). Data obtained by ELISA, significantly correlated with those obtained by HPLC (r = 0.990). It required no clean-up for water samples and less clean-up steps (than HPLC) in soil/coloured extracts, but showed matrix effect. Validation showed good accuracy and precision thereby suggesting that this test can be applied accurately for atrazine detection in water. This IA experience demands future IAs development in Pakistan for commonly used pesticides.